Digital Transformation and Innovation Capability Effects on Marketing Performance - Fajar Nugroho; Adya Hermawati; Ana Sopanah (International Journal of Multidisciplinary Sciences and Arts, 2026)
This study examines the influence of digital transformation, innovation capability, social media marketing, and market turbulence on marketing performance among creative economy players in Malang City. It also analyzes the mediating role of social media marketing in the relationship between digital transformation and innovation capability with marketing performance, as well as the moderating role of market turbulence in the relationship between social media marketing and marketing performance.The study adopts a quantitative approach with a cross-sectional design. The population consists of 4,951 creative economy business players in Malang City, with a sample of 196 respondents determined using the Slovin formula. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software, including descriptive analysis, validity and reliability testing, and hypothesis testing through bootstrapping.The results indicate that digital transformation has a significant positive effect on marketing performance, while innovation capability does not. Digital transformation and innovation capability significantly improve social media marketing, which in turn has a significant positive effect on marketing performance. Market turbulence has a significant negative effect on marketing performance and significantly moderates the relationship between social media marketing and marketing performance. Social media marketing significantly mediates the effects of digital transformation and innovation capability on marketing performance.